Regional differences in the temporal expression of nonapoptotic caspase-3-positive Bergmann glial cells in the developing rat cerebellum - Finckbone, VelvetLee; Oomman, Sowmini S.; Strahlendorf, Howard K.; Strahlendorf, Jean C. (Frontiers in Neuroanatomy, 2009)
Although caspases have been intimately linked to apoptotic events, some of the pro-apoptotic caspases also may regulate differentiation. We previously demonstrated that active caspase-3 is expressed and has an apparent non-apoptotic function during the development of cerebellar Bergmann glia. The current study seeks to further correlate active/cleaved caspase-3 expression with the developmental phenotype of Bergmann glia by examining regional differences in the temporal pattern of expression of cleaved caspase-3 immunoreactivity in lobules of the cerebellar vermis. In general, we found that the expression pattern of cleaved caspase-3 corresponds to the reported developmental temporal profile of the lobes and that its levels peak at 15 days and declines thereafter. Compared to intermediate or late maturing lobules, early maturing lobules had higher levels of active caspase-3 at earlier postnatal times. This period of postnatal development is precisely the time during which Bergmann glia initiate differentiation.